ANALISIS PENGGUNAAN JEJARING MEDIA SOSIAL SEBAGAI SARANA PROMOSI LAYANAN PERPUSTAKAAN DI SMP 1 PROPPO PAMEKASAN - Andini, Dian Nuri (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to analyze the use of social media networks, especially Instagram and the SLIMS (Senayan Library Management System) application, which can be used to promote library services at SMP 1 Proppo. This research also investigates how the use of social media and digital applications can increase students' interest in libraries and literacy. This study utilizes a qualitative descriptive approach. Data was collected through observing promotional activities on social media, interviews with librarians and students, and documenting content posted on Instagram and SLIMS. Data analysis was carried out using data reduction methods, data presentation, and conclusions. The research results show that Instagram is used to publicize library activities, such as literacy competitions, the latest book collections, and digital literacy campaigns. Meanwhile, managing library data, borrowing books, and available book collections is made easier with the SLIMS application. The increase in the number of visits and book borrowings shows that the use of these two platforms increases student participation. However, technical issues such as lack of employee training and technological infrastructure are obstacles. This article has great benefits for science, especially in terms of the use of digital technology to encourage literacy. These results can help other school libraries develop innovative and flexible digital-based services. These results can help other school libraries develop innovative and flexible digital-based services.